2007
DOI: 10.1007/s10464-007-9123-2
|View full text |Cite
|
Sign up to set email alerts
|

A Community Psychology View of Environmental Organization Processes

Abstract: Environmental organizations have a key role in addressing environmental degradation and promoting ecologically and socially sustainable societies. Psychosocial processes underpin their work, however, empirical studies of these processes remain underdeveloped. This paper presents the first stage of a community psychology study involving in-depth interviews with leaders in environmental organizations. Qualitative analysis revealed a framework of five types of psychosocial processes that assist environmental orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 67 publications
(67 reference statements)
1
12
0
Order By: Relevance
“…This is in line with what is known from other areas of community studies, where it was shown how joint action achieves better results than transfer of knowledge (Dewulf et al 2004;Bowen and Taillieu 2004). This holds even when the transfer of knowledge takes place early in the project (Dean and Bush 2007), as this top-down approach is a way of pre-setting the issues for discussion (Culley and Hughey 2008).…”
Section: The Dialogical Approach As a Tool For Biodiversity Conservationsupporting
confidence: 89%
See 2 more Smart Citations
“…This is in line with what is known from other areas of community studies, where it was shown how joint action achieves better results than transfer of knowledge (Dewulf et al 2004;Bowen and Taillieu 2004). This holds even when the transfer of knowledge takes place early in the project (Dean and Bush 2007), as this top-down approach is a way of pre-setting the issues for discussion (Culley and Hughey 2008).…”
Section: The Dialogical Approach As a Tool For Biodiversity Conservationsupporting
confidence: 89%
“…Indeed, the field of ecological conservation now offers some examples of how to integrate knowledge from several sources (Barbanente and Monno 2005;Dean and Bush 2007). These examples attest to the fact that it is possible to create hybrid discourses which draw simultaneously from local knowledge and policy making, in a process creating different types of resources for coping with adversities and risks (Barbanente and Monno 2005).…”
Section: The Dialogical Approach As a Tool For Biodiversity Conservationmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculate that social well-being could be one of the key processes that explains this impact. In addition, a role in the promotion of ecologically and socially sustainable societies is played by citizen involvement in the wider community and its social institutions, as it is implied in the concept of community participation (e.g., Bott et al, 2003;Dean & Bush, 2007;Prati et al, 2016). As such, interventions aimed at promoting pro-environmental choices should not only strengthen the added value and psychological gains of becoming part of a righteous community, but also offer concrete opportunities to experience community participation.…”
Section: Discussionmentioning
confidence: 99%
“…This willingness to venture into new, potentially beneficial, arenas enabled them to seize opportunities that less-enterprising coalitions may have missed. Dean and Bush (2007) noted that coalitions that are more open and inclusive in their approach are more likely to progress in systems change and paradigm-shifting activities. A common condition of coalitions that gained less traction with their work was an absence of strong community involvement, which is also an important component of sustainability.…”
Section: Coalition Engagement In Policy Advocacymentioning
confidence: 99%